2017
DOI: 10.1016/j.gie.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Providing data for serrated polyp detection rate benchmarks: an analysis of the New Hampshire Colonoscopy Registry

Abstract: Background and Aims Similar to achieving adenoma detection rate (ADR) benchmarks to prevent colorectal cancer (CRC), achieving adequate serrated polyp detection rates (SDR) may be essential to the prevention of CRC associated with the serrated pathway. Previous studies have been based on data from high-volume endoscopists at single academic centers. Based on a hypothesis that ADR is correlated with SDR, we stratified a large, diverse group of endoscopists (n=77 practicing at 28 centers) into high and low perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(131 citation statements)
references
References 27 publications
11
116
4
Order By: Relevance
“…The authors found a surveillance SSPDR of 10%, which is in the range of that found in our cohort (8%) [15]. A more recent multicenter study by Anderson and colleagues investigated proximal colon SSPDR for surveillance colonoscopy and found that among endoscopists with > 35% ADRs, median proximal SSPDR was 14.7% [10]. Our data are congruent as we also found that greater endoscopists’ screening ADR is associated with greater SSPDR.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The authors found a surveillance SSPDR of 10%, which is in the range of that found in our cohort (8%) [15]. A more recent multicenter study by Anderson and colleagues investigated proximal colon SSPDR for surveillance colonoscopy and found that among endoscopists with > 35% ADRs, median proximal SSPDR was 14.7% [10]. Our data are congruent as we also found that greater endoscopists’ screening ADR is associated with greater SSPDR.…”
Section: Discussionsupporting
confidence: 89%
“…The most recent benchmark for screening ADR is an average of 25% (women 20% and men 30%) [2]. Though there is currently no benchmark for sessile serrated polyp detection rate (SSPDR), prior studies have found varying rates, reporting up to 18% in screening examinations and up to 15% in surveillance examinations [810]. …”
Section: Introductionmentioning
confidence: 99%
“…33,34 Anderson et al believe a benchmark of 11% should be appropriate. 35 In the current study, the effectiveness of CWE and WE is well demonstrated by the significantly higher detection rate of the even more subtle proximal colon SLs by CWE (26.3%) and WE (23.6%) over AI (11.3%). By enhancing the outline of underlying lesions, chromoendoscopy does improve the detection of smaller SLs, especially in the proximal colon.…”
Section: Discussionsupporting
confidence: 65%
“…45,62,73 Reviews of recently published colonoscopy series studies found that an average 2%-8% of SSLs are detected (akin to prevalence) in average-risk patients undergoing colonoscopy. 8,54,58,62,[73][74][75][76][77][78][79][80][81][82] Among high-detecting endoscopists and centers, however, the reported prevalence values are 13%-20% ( Figure 3A, Supplementary Table 2). 45,54,62,74,78 It is a reasonable assumption that detection of SSLs among high detectors is the best estimate of the true prevalence of these lesions.…”
Section: Prevalence Based On Endoscopic Datamentioning
confidence: 99%